EMISSION PROCESSES OF QUANTUM WELL INTERACTION WITH DELTA-LAYER IN pHEMT-HETEROSTRUCTURES - Yana V. Ivanova; George E. Yakovlev; Vasily I. Zubkov (Известия высших учебных заведений России: Радиоэлектроника, 2018)
The paper provides experimental and theoretical study of pHEMT heterostructures with quantum well (QW) AlGaAs/InGaAs/GaAs and delta-doped layer used as active layers for fabrication of 4-18 GHz transistors. As the experimental techniques, the electrochemical capacitance-voltage (ECV) profiling and other methods of admittance spectroscopy are applied. Modernization of commercial ECV-profiling setup allows observing for the first time the concentration peak from a near-surface delta-layer of pHEMT heterostructures together with the enrichment peak from the quantum well. In order to optimize the etching speed the crater bottom control is performed by means of AFM. The electrolyte-semiconductor contact capacitance is measured with Agilent RLC-meter. The main theoretical technique used in the research is numerical modeling of nanoheterostructure key electronic features by self-consistent solution of Schrödinger and Poisson equations. The potential line-up for the conduction band bottom is obtained, and the quantized energy levels are calculated. The complex analysis of series of samples is carried out in order to understand the influence of delta-layer position on the level depth and at the carrier concentration. The optimum distance between QW and delta-layer providing the most efficient charge carrier delivery to quantum well is found. The performed research is aimed at improvement of microwave electronic devices allowing increase of the gain coefficient and the transfer characteristic of SHF-transistors.